Efficacy of antibiotic prophylaxis on postoperative inflammatory complications in Chinese patients having impacted mandibular third molars removed: a split-mouth, double-blind, self-controlled, clinical trial. Issue 5 (May 2015) - Xue, P.; Wang, J.; Wu, B.; Ma, Y.; Wu, F.; Hou, R.
Abstract We investigated the effect of antibiotic prophylaxis on postoperative inflammatory complications after operations for impacted mandibular third molars in Chinese patients. A total of 207 patients had their bilateral third molars removed in a split-mouth, double-blind, self-controlled, clinical trial in two visits. For one side amoxicillin (or clindamycin) was given (antibiotic group) from one hour before operation until 3 days postoperatively. For the other side a placebo was given (placebo group) at the same time. The outcome, including alveolar osteitis, surgical wound infection, prebuccal infection, and infection of the anterior isthmus of fauces, was assessed 2 and 10 days postoperatively. A total of 192 patients completed the study, and there was no difference between the groups in the incidence of inflammatory complications. In the treatment group, there were 4 cases of alveolar osteitis (2%), 2 infections of the wound (1%), and 14 other reactions (gastrointestinal (n = 4), bleeding (n = 2), ulcer (n = 2), and fever (n = 6)). In the placebo group, there were 6 cases of alveolar osteitis (3%), 2 wound infections (1%), and 22 other reactions (bleeding (n = 6), ulcer (n = 2) and fever (n = 14)). There was no significant difference in the extraction time and postoperative reactions, except the pain score on day 10 (p = 0.005). Prophylactic amoxicillin (or clindamycin) is not effective for the prevention or reduction of postoperative inflammatory complications after the removal of impacted mandibular third molars in Chinese patients.